The Forced Displacement Crisis : A Ioint Paper by Multilateral Development Banks - African Development Bank; Asian Development Bank; European Bank for Reconstruction and Development; European Investment Bank; Inter-American Development Bank; Islamic Development Bank; World Bank Group (Washington, DC: World Bank, 2017)
Recent events have drawn the world’s attention to a crisis that has been building up for a long time—forced displacement. Beside five million Palestinians, over half of the refugees worldwide originate from Syria, Afghanistan and Somalia – with Sudan, South Sudan, the Democratic Republic of Congo (DRC), Myanmar, Iraq, and Eritrea also accounting for large numbers. This joint paper aims to define a framework for collective action for Multilateral Development Banks (MDBs) in response to the forced displacement crisis, within the context of the One Humanity agenda issued by the United Nations Secretary General in February 2016. The paper outlines an agenda for MDBs to further strengthen their contributions, complementing humanitarian, diplomatic and peacekeeping efforts in specific areas where stronger synergies are desirable and possible. This paper was jointly coordinated by the European Investment Bank (EIB) and the World Bank Group (WBG) and prepared by MDB staff. The paper has three main sections focusing on MDBs’ strategic agenda as they attempt to mitigate and or respond to the crisis (Section B); operational implications of this response in terms of financial instrument, organizational challenges (Section C); and, finally a framework for collective action (Section D). Annexes I to III provide additional definitions and numbers.